2009
DOI: 10.1515/sg-2009-0013
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance Pattern of Growth and Wood Traits in Teak (Tectona grandis L.f.).

Abstract: Inheritance pattern of wood traits, especially heartwood/ sapwood percentage and specific gravity and interactions of wood traits with other growth traits were investigated in a 27-year-old half-sib progeny trial of teak. Wood traits showed highly significant variation for specific gravity, heartwood and sapwood percentage at family level. There was non-significant family vs. replication variation for these traits. Among the growth traits, there was significant variation for height and girth. Families and indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 4 publications
2
7
0
3
Order By: Relevance
“…On the second hand, Cetropic and Hojancha C2008 reproduction materials show the lowest mean total height, mean DBH and mean growing stock when comparing all of reproduction materials. These results confirm Narayanan et al (2009) which prove a significant dependence of growth characteristics and timber quality on heredity.…”
Section: Proveniencesupporting
confidence: 84%
See 1 more Smart Citation
“…On the second hand, Cetropic and Hojancha C2008 reproduction materials show the lowest mean total height, mean DBH and mean growing stock when comparing all of reproduction materials. These results confirm Narayanan et al (2009) which prove a significant dependence of growth characteristics and timber quality on heredity.…”
Section: Proveniencesupporting
confidence: 84%
“…A several authors describe difference growth parameters, wood quality, ecology condition or plant clones of the used proveniences (Pedersen et al, 2007;Narayanan et al, 2009;Husen, 2010;Isotupa and Tyynela, 2010). Comparison of wood quality was impossible.…”
Section: Proveniencementioning
confidence: 99%
“…Heritability of 0.27 is low for HWP but similar in families of T. grandis of similar age (MURILLO and BADILLA, 2004). But NARAYANAN et al (2009) found high heritability (Ĥ 2 = 0.77) in the HWP for 27 year old trees. Nonetheless, this low heritability found in our study or those obtained by CALLISTER and COLLINS (2008) in 4-year-old T. grandis should be taken with great caution.…”
Section: Heritability Of Wood Propertiesmentioning
confidence: 87%
“…Although these are considered to be low, they are relevant for the manifestation of character for future "ramets" (CALLISTER and COLLINS, 2008). In a study with clones of 3.5 years old T. grandis, CALLISTER and COLLINS (2008), SWAIN et al (1999) and NARAYANAN et al (2009) have found a value of Ĥ 2 of 0.28, 0.38 and 0.34, respectively for tree height, which authors considered low but relevant. But SWAIN et al (1999) found too high Ĥ 2 with 12 years old trees.…”
Section: Heritability Of Wood Propertiesmentioning
confidence: 99%
“…Domestication and tree improvement were initiated in Thailand, India and Indonesia in the 1950s and 1960s and was followed up based on comprehensive selections of superior plus-trees in these countries (Keiding et al 1986;Kjaer and Foster 1996;Kaosa-ard et al 1998). Since then, improvement activities have been initiated in many countries (Kjaer et al 2000), and genetic parameters estimated based on progeny and clonal trials in general predict good response to breeding (Mandal and Chawhan 2005;Callister and Collins 2008;Narayanan et al 2009;Callister 2013).…”
Section: Introductionmentioning
confidence: 99%